The Word universe a journey to West Africa [videorecording] - Keegan, Mark; Marley, Bob ([Studio 1605], 1995)
An American visits his African friend, who has fled with his family from their home in Liberia to the Ivory Coast. Film examines the personal costs of the civil war raging in Liberia upon the refugees.